The Legal Certainty of Community Participation Related to Mining Activities - Tampubolon, Muhammad Hatta Roma; Maddusila, Sitti Fatimah; Zulkarnain, Zulkarnain; Mallawa, Suardi Dg. (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
Indonesia is rich in mining resources, which constitute one of the crucial sectors for national development. However, mining activities are not without controversy, particularly regarding community participation in decision-making processes and implementation. Despite existing laws guaranteeing the community's right to participate, their implementation still faces obstacles such as legal uncertainties concerning the mechanisms and procedures for participation, which have not been clearly and comprehensively regulated. The purpose of this research is to examine the legal certainty regarding community participation in mining activities in Indonesia and to identify the problems and challenges faced in its implementation. This study employs normative legal research methods with a legislative and conceptual approach. Data collection techniques are conducted through literature studies, analyzed qualitatively with content analysis, and presented descriptively and analytically. The research findings reveal that legal certainty regarding community participation in mining activities in Indonesia is currently regulated by laws such as the Mineral and Coal Mining Law (UU Minerba) and Government Regulation No. 51/2014, which guarantee the community's right to participate. However, these regulations do not clearly define the mechanisms and procedures, leading to legal uncertainty. The main problems and challenges in implementation include unclear mechanisms and procedures for participation, lack of socialization and transparency of information, low community capacity, weak law enforcement and supervision, and potential conflicts of interest that can hinder effective and sustainable community participation in mining activities.